Vaccination with EG95 against ovine cystic echinococcosis in the province of Río Negro: analysis of 12 years of work (Veterinary Science, 2022)
Cystic echinococcosis (CE) is a zoonosis caused by species of the complex Echinococcus granulosus, sensu lato in their larval stage. It is an endemic disease in the province of Río Negro, where lamb vaccination with EG95 was incorporated in 2009 with very good results: in fact, it contributed to a significant drop in prevalence of infection in diverse hosts. However, impact studies have revealed the need to improve understanding of local epidemiology. The objective was to identify causes which can still generate infection in dogs. In indigenous reserves comprised within the area of lamb vaccination with 3 doses of EG95, prevalence in adult caprines and ovines was determined by necropsy and serology (ELISA). Through serology, infection rates in vaccinated and non-vaccinated ovines were significantly different (p= 0.0004), as well as between non-vaccinated ovines and goats (p= 0.0013); on the other hand, infection rate differences between vaccinated sheep and non-vaccinated goats turned out non-significant (p= 0.254). Through necropsy, such difference between vaccinated and non-vaccinated ovines turned out significant (p= 0.0016); between non-vaccinated ovines and non-vaccinated goats, it proved non-significant (p= 0.23). With reference to epidemiology and control along the period 2018- 2022, vaccination strategy was maintained, and 2 extra deworming tasks were introduced, performed by the vaccination team. Assessment of animal slaughter for consumption in 41 producers showed that 21 of them slaughter a monthly average of 18 goats, and 36 in all slaughter 35 old sheep. Design and implementation of programme resulted cost-effective, since it was possible to maintain them over time, with clear impact on prevalence decrease in diverse hosts
Keywords: Echinococcosis; Epidemiology; Vaccine; Sheep